Environmental restoration through soil conservation. A case study of Monte Gibralfaro (Málaga, Spain). - Moreno Alarcón, Concepción; Sillero-Medina, José Antonio; Ruiz-Sinoga, José Damián (My University, 2024)
Soil conservation in natural areas within urban settings is essential to ensure environmental sustainability. These spaces act as green lungs, providing crucial ecosystem services such as carbon sequestration, water regulation and habitats for biodiversity. Proper land management in these urban areas contributes to air quality, human health and resilience to extreme weather events, promoting a balance between urban development and environmental preservation. In a context of climate change, especially in highly vulnerable areas such as the Mediterranean, land degradation processes are one of the main threats. Therefore, the development of sustainable strategies for the evaluation and characterisation of soils, as well as the conservation, restoration and renaturalisation of these spaces is a key factor in land management. Underthese premises, the current work focuses on an urban forest area in the city of Malaga (Spain) - Monte Gibralfaro - characterised by low biodiversity and a lack of territorial connection with the natural matrix, which makes it more vulnerable to the effects of climate change. The objectives of this research are: (i) todetermine soil erosion rates using the RUSLE model; (ii) to estimate SOC stocks as an indicator of soil health; (iii) to evaluate the dynamics of vegetation cover in recent years using spatial remote sensing techniques; and (iv) to promote strategies and actions for soil conservation and the improvement of ecosystem services. In short, the work aims to provide a general characterisation and diagnosis of the state of soil health and, subsequently, to design different actions focused on the restoration of soils as an essential component of environmental dynamics.
Keywords: Impacto ambiental - Málaga; Suelos - Conservación; SOC stocks; Degradation; Ecosystem services; Environmental restoration; Soil conservation